An environmental monitoring system for the availability of drinking water for the population as an ecosystem service in areas exposed to covid-19. Issue 1 (1st February 2022) - Samadi, S; Suhardjo, S; Munandar, A
Abstract: An effectiveness of the protected or rehabilitated natural assets will provide information on the availability of natural resources to respond to the impacts of climate change and ecosystem health. The emergence of the COVID-19 pandemic disaster increasingly shows that if humans destroy biodiversity, it also destroys human life-support systems. The purpose of the research to obtain a dynamic-empirical description of the availability of clean water for drinking water for residents in areas exposed to the Covid-19 pandemic as an implementation of an environmental monitoring system for ecosystem services. The research method uses quantitative methods. The results showed that: (1) although the low pressure area affected the number of customer complaints, it was not entirely the main factor that most dominantly affected the number of complaints of small water, dead water, and water quality in the studied area. (2) The results of the R square regression test show the percentage of the influence of low pressure areas on complaints of small water complaints, dead water, and water quality; is below 100%. The conclusion shows that although low water pressure occurs in areas exposed to Covid-19 in DKI Jakarta, it does not always affect customer complaints. This is because low water pressure is not entirely caused by small water, dead water, or water quality. Therefore, the environmental monitoring system for the availability of drinking water for the population as an ecosystem service pays more attention to other parameters besides small water, dead water, and water quality.